1993
DOI: 10.4039/ent1251033-6
|View full text |Cite
|
Sign up to set email alerts
|

DISTRIBUTION AND ABUNDANCE OF LYGUS SPP. (HETEROPTERA: MIRIDAE) ON ALFALFA AND CANOLA IN MANITOBAf

Abstract: Lygus species were sampled from alfalfa and canola fields in Manitoba from 1988 to 1990. Lygus lineolaris (Palisot de Beauvois), L. borealis (Knight), and L. elisus (Van Duzee) were found consistently throughout the agricultural area. The relative abundance of these species varied among crops, physiographic regions, years, and date of collection. The most abundant species in alfalfa and canola fields tended to be L. borealis in the north and west, L. elisus in the south, and L. lineolaris in the east. Each of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…Colonizing adults, nymphs, or new-generation adults were present on the rosette, bud, flower, or pod development stages of canola, indicating that these species all reproduce and develop populations on this crop in Manitoba. Schwartz and Foottit (1992) and Timlick et al (1993) also found L. lineolaris to be the dominant species on canola in the Red River region of Manitoba (the region in which Glenlea is located) from 1988 through 1990. However, the species assemblage on canola varies with location and year of collection.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Colonizing adults, nymphs, or new-generation adults were present on the rosette, bud, flower, or pod development stages of canola, indicating that these species all reproduce and develop populations on this crop in Manitoba. Schwartz and Foottit (1992) and Timlick et al (1993) also found L. lineolaris to be the dominant species on canola in the Red River region of Manitoba (the region in which Glenlea is located) from 1988 through 1990. However, the species assemblage on canola varies with location and year of collection.…”
Section: Discussionmentioning
confidence: 93%
“…The simultaneous occurrence of more than one Lygus species on canola and other crops is common (Fye 1982;Craig 1983;Domek and Scott 1985;Butts and Lamb 1991;Schwartz and Foottit 1992;Timlick et al 1993). Colonizing adults, nymphs, or new-generation adults were present on the rosette, bud, flower, or pod development stages of canola, indicating that these species all reproduce and develop populations on this crop in Manitoba.…”
Section: Discussionmentioning
confidence: 99%
“…The most common Lygus species present in Manitoba crops are Lygus lineolaris (Palisot de Beauvois), Lygus borealis (Knight), and Lygus elisus (Van Duzee) (Timlick et al 1993;Gerber and Wise 1995;Mostafa 2007). Adults of Lygus species overwinter in litter and crop residues (Kelton 1975) and nymphs develop through five instars (Schwartz and Foottit 1992a).…”
Section: Introductionmentioning
confidence: 99%
“…For example, they often move from alfalfa to canola (Timlick et al, 1993) or oil seed rape (Butts & Lamb, 1991) within a season. In southern Quebec, this pest is successively observed on natural vegetation like white clover (Trifolium pratense) early in the season and goldenrod (Solidago canadensis) late in the season (Boivin & Stewart, 1983).…”
Section: Introductionmentioning
confidence: 99%